Penerapan Modular Smart PJU di Daerah Keputih Surabaya - Bachtiar, Mochamad Mobed; Wibowo, Iwan Kurnianto; Marta, Bayu Sandi; Ardilla, Fernando (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Street lighting is an important aspect of village infrastructure that affects the safety and mobility of the community. However, many villages still rely on manual systems to manage street lighting, causing inefficiencies in energy management and uncertainty in the availability of adequate lighting. The implementation of Smart PJU technology offers a solution to improve the efficiency, control, and monitoring of street lighting. However, the adoption of this technology is hampered by funding constraints and the availability of adequate devices. This study aims to develop and implement Smart PJU technology in Keputih Village, Indonesia, by involving collaboration between the Computer Engineering Study Program of PENS, village officials, and the local community. The resulting product, namely the Smart PJU Modular Device using Wireless technology, not only includes hardware for monitoring and controlling PJU lights, but also provides added value through increasing the level of domestic content (TKDN) and developing research in the Internet of Things (IoT). With this product, it has provided significant benefits to the people of Keputih Village, thus supporting and improving the quality of village infrastructure, as well as encouraging participation in the development of sustainable technology. Through this community service, the Keputih Village Community has obtained a practical solution to the problem of public street lighting and spurred innovation at the local level. Smart PJU has been installed on the PJU lights in the Keputih five-way intersection area and in front of the Keputih Village entrance. Smart PJU has been integrated with the website https://desabinaan.pens.ac.id/, where it can be monitored online whether the PJU lights are on or not, the voltage and current values ​​that flow, and allows you to control the lights remotely.